Case Series of Post Covid-19 Vaccine Cervical Lymphadenopathy - Sher Ali Khan, Ahmad Nayef Habahbeh ,Mohammad Alsyed Abdul Hadi, Sher Ali Khan, Ahmad Nayef Habahbeh ,Mohammad Alsyed Abdul Hadi (Journal of Rawalpindi Medical College, 2022)
Objective: The objective of this case series reporting is to add cervical lymphadenopathy as one of the side effects of the COVID-19 vaccine in the adult population presenting with neck swelling. Materials and Methods: This case series of twenty patients were collected at our facility over a period of six months, from March 2021 to the end of August 2021, with an age interval from 17 years to 52 years. The Post COVID Vaccine window to develop cervical lymphadenopathy was from the 3rd day till the 16th. All patients received their first dose of the COVID vaccine. Results: Out of all the patients, 16 were females and 4 were males. Six female and one male patient developed suppurative ipsilateral upper cervical lymphadenitis, which necessitated hospitalization and surgical intervention with incision and drainage, as well as IV medications. Five patients were admitted by internal medicine for workup and supportive care as they were having generalized symptoms, such as fever, chills, headache, myalgia, and inadequate oral intake. The OMFS department was called for evaluation and to rule out any oral infection. Four patients were diabetics with a mean HbA1C of 6.7% to 7.5%. All of these patients did not have any active dental or salivary gland infections. Eventually, all subjects fully recovered with no residual lymphadenopathy and were followed for a period of two weeks to two months, using ultrasound. Conclusion: Cervical Lymphadenopathy and suppurative lymphadenitis have become increasingly common in patients who received the COVID-19 vaccine. Therefore, it must be referenced for the differential diagnosis of neck swelling, especially during this time.